Scanning Fuel Tanks’ Corrosion Wastage of Some Aged Bulk Carriers Due to Security Reasons - Bauk, Sanja; Aleksić, Marinko; Ivošević, Špiro (Promet - Traffic&Transportation, 2012)
This paper deals with two different approaches in modelling corrosion wastage over the fuel tanks’ structures on the example of ten aged bulk carriers. The first applied method might be treated as a short-term, rather random oriented one, and it is based on the Monte Carlo simulation technique. This technique has been used in creating an appropriate predictive model for the characteristic steel damages over the bulk carriers’ fuel tanks caused by general corrosion in relatively short time interval of two years, within the period between the 5th and the 25th year of the bulks’ operational life. The second employed method might be treated as a long-term one, and it is based on a Weibull distribution analysis. The purpose of these analyses is optimal assessing of the average corrosion losses for the bulk carriers’ fuel tanks areas at different points of time during the whole exploitation cycle, within the ultimate goal of raising the structural stability and safety of bulk carriers in operation. KEY WORDS: bulk carriers, fuel tanks, corrosion wastage, Monte Carlo simulation, Weibull probability analysis